The formation of the contractual regulation in the in the field of human prosthetics - Тараненко, Анна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The regulations on issues, related to human prosthetics, the shortcomings of the legal regulation of contracts conclusion in prosthetic ware manufacturing, service and prosthetic medical service at all stages of such legislation formation are analyzed and researched in the article. Legislation on issues, related to prosthetics consists of two groups of such acts: the regulations of social security law, regulating social and medical prosthetics public relations in the field of prosthetics, which are partly private (those relating to contract conclusion, and those, which are related to the subjects, that are not included in the list of persons entitled to free state prosthetic ware providing); and civil law rules, governing similar contractual relations, certain features of which allow us to include prosthetic relations to certain types of contracts (contracting relations and services providing relations, including medical).